Electromagnetic analysis of a coaxial metal disc loaded waveguiding structure - Dixit G.; Jain P.K. (My University, 2025)
A metal disc-loaded coaxial cylindrical waveguiding structure is analyzed using field analytical approach for the TM mode of operation. The structure parameters are obtained in terms of equivalent inductance per unit length, capacitance per unit length and susceptance per unit length of the equivalent transmission line model. The developed analysis though yields the same results as that of field analysis and less involved and cumbersome. The structure is also simulated for its EM behavior using 3D simulation code CST Design Studio. The simulation and analytical results are found to be in close agreementâ © 2015 IEEE.